Penerapan Model Pembelajaran Poe (Prediction, Observation And Explanation) Pada Materi Fotosintesis Terhadap Hasil Belajar Siswa Kelas Viii Semester Genap Di Smp N 22 Surakarta Tahun Pelajaran 2015/2016 - KHOIRINA MIFTAHURROHMAH, SHOFFI; Anif, M.Si se, Dr. Sofyan Anif, M.Si se (2016)
Biology as one part of science has crucial role in education. Unforturately the ability or the mastery of Biology is still low. Goverment always tries to motivate teachers to improve the quality of teaching and learning process in order the result of the learning outcome increases. The objective of the research is to know the influence of teaching using POE in photosynthesis material. The method of the research was quasy experiment. The population was class VIII SMP N 22 Surakarta 2015/2016 Academic Year. The sample was taken with the purposive sampling which was divided inti control class (VIII D) which was taught by conventional method and experimental class (VIII E) which was taught by POE teaching model. The data were got through the result of the students test. Hypothesis test used was Independent Sample t Test. Based on the result of the data it can be drawn that teaching using POE is more effective than conventional method to teach phtosynthesis material. It is hoped that the result of the reseach can be useful to determine and select the suitable teaching model to teach the students. The conclusion is there is an influence using POE in the teaching learning process.